Multiyear measurements on 15N natural abundance of precipitation nitrate at a rural forested site. (15th May 2021) - Huang, Shaonan; Fang, Yunting; Zhu, Feifei; Elliott, Emily M.; Felix, J. David; Wang, Fan; Li, Shanlong; Liu, Dongwei; Song, Linlin; Li, Zhengjie; Fu, Pingqing; Fu, Shenglei
Abstract: Large anthropogenic NO x emissions increase atmospheric nitrate (NO 3 − ) deposition. The China's Clean Air Action has been implemented to reduce anthropogenic NO x emissions since 2013. To examine if atmospheric NO3 − deposition would decrease and its sources had changed as a result of this regulation, we collected the precipitation samples (n = 181) on a daily basis at a rural forested site in Northeast China from April 2014 to December 2017 and measured the concentrations and δ 15 N values of NO3 − . We found annual NO3 − deposition ranged from 6.5 to 7.3 kg N ha −1 yr −1 and gradually declined since 2015. The δ 15 N–NO3 - spanned a large range from −17.4 to 13.1‰ with a mass-weighted mean of −3.5‰ during the study period. The δ 15 N–NO3 - was higher by 10‰ in winter (3.3 ± 4.2‰) than in summer (−7.4 ± 3.9‰), which was driven by the changes of both coal combustion and soil emission. Over the study period, NOx from coal combustion, vehicle exhaust, biomass burning and soil emission contributed 28.2 ± 11.9%, 28.8 ± 16.3%, 26.9 ± 14.7%, and 16.1 ± 7.2% to precipitation NO3 −, respectively. We found that relative contribution of fossil fuel combustion did not decline with the China's Clean Air Action and considerable NO x reduction at the regional scale . Graphical abstract: Image 1 Highlights: The δ 15 N values of NO3 − in rain were measured at a rural site over four years. Nitrate deposition only decreased 6% while NOx emission was reduced by 27%. The contributions of varied NOx sources to NO3 − deposition unchanged among years. Fossil fuel combustion still was dominant NOx source even with a sharp NOx decline. Coal combustion and soil emission determined seasonal δ 15 N–NO3 - trend. Abstract : We found that relative contribution of fossil fuel combustion did not decline with the China's Clean Air Action and considerable NOx reduction at the regional scale.